(3GdLfi GdOGfj aj MQha GdeYGfjs - (3GdeQGOj GdeUQj, CHh eMeO, HOQ GdOjf, GHf Ce bGSe, GHf Ce bGSe, GdMSf Hf bGSe Hf YHO Gddg GdeQGOj GdeUQj, J (B749(3g` (B1348(3es ((3eMeO WGgQ GdSeGhjs)
(3ChdgG (B:s
(3ChdgG(B: (3GdMeO ddg HLejY eMGeOg (B... (3gPG cJGH CQLhG Cf jchf fGaYG hdeYGfj GdMQha LGeYG (B... (3hjTJed Ydi ebOeI hNeSI CHhGH , GdebOeI ajgG NeSI aUhd, GdaUd GdChd aj gPG GdMQas
(3BNQgG (B:s
(3BNQgG(B: (3hbO cGf MJi gPg GdCdaGX Cf CPcQgG aj HGH GdKdGKj hGdQHGYj, EfeG GLdJ PcQgG gfG dTgQJgG hZQGHI Gdbhd HMQajJgG hGdcdGe YdjgG ehVY gh GdeHfj Hg aj gPG GdcJGHs
(3efShN Yf fSNI SbjeIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B2: 211s
(3cTa GdXfhf, L (B1: 607s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
Keywords: (3GdfMhs